CORRELATION OF HEALTH LITERATURE WITH CLEAN AND HEALTHY LIVING BEHAVIOR IN THE EFFORT TO BREAK TRANSMISSION OF THE COVID-19 - Setiadi; Priyantini, Dwi; Dedi Irawandi (Journal of Islamic Nursing, 2022)
The application of disease prevention behavior is influenced by the level of health literacy which consists of aspects of information, knowledge, understanding, and decision making. The purpose of this study was to determine the relationship between health literacy and a Clean and Healthy Lifestyle to break the chain of transmission of the Covid 19 pandemic in STIKES Hang Tuah Surabaya students. The research design used was analytic observational with a cross sectional approach. The results of the analysis of health literacy related to Clean and Healthy Living Behavior to break the chain of transmission of the Covid 19 pandemic in STIKES Hang Tuah Surabaya students. The implication of the research is that adequate health literacy will increase students' abilities on Clean and Healthy Life Behavior (PHBS) to break the chain of transmission of the Covid 19 pandemic in STIKES Hang Tuah Surabaya students